Sternoclavicular Joint Instability: Symptoms, Diagnosis And Management - Garcia JA; Arguello AM; Momaya AM; Ponce BA (Orthopedic Research and Reviews, 2020)
Jacob A Garcia,1 Alexandra M Arguello,2 Amit M Momaya,2 Brent A Ponce2 1University Of Alabama At Birmingham School Of Medicine, Birmingham, AL 35294, USA; 2University Of Alabama At Birmingham, Department Of Orthopedic Surgery, Birmingham, AL 35294, USACorrespondence: Brent A PonceDepartment of Orthopaedic Surgery, University Of Alabama At Birmingham, Birmingham, AL 35294, USATel +1 205-930-7081Fax +1 205-930-8981Email bponce@uabmc.eduAbstract: Sternoclavicular joint (SCJ) instability is a rare condition and results from either a traumatic high energy impact, such as a motor vehicle crash or contact sports injury, or non-traumatically as a result of structural pathology. The infrequency of this injury has contributed to its diagnosis being missed as well as the paucity of literature on treatment and outcomes. Patients with SCJ instability often report diminished range of motion as well as shoulder girdle pain. The presentation of instability in the sternoclavicular joint can vary in severity and anterior or posterior directionality. Variation in severity of the instability changes the course of treatment regarding either operative or non-operative interventions to stabilize the SCJ. In general, anterior instability of the SCJ (the medial clavicle is displaced anterior to the sternum) is less urgent and generally manageable by symptom alleviation and rehabilitation, although some anterior instability cases require surgical intervention. In the case of posterior SCJ instability (the medial clavicle is displaced posterior to the sternum), patients require prompt joint reduction as they are at the greater risk of life-threatening injury due to the location of critical structures of the mediastinum posterior to the SCJ. Computed tomography visualization is useful to confirm dislocation or subluxation direction to better formulate a proper treatment plan. The purpose of this review is to report the clinical presentation and management of SCJ instability including pertinent symptoms, the diagnostic approaches to evaluating SCJ instability, as well as operative and non-operative management of the joint instability.Keywords: sternoclavicular joint instability, SCJ dislocation, surgical techniques